2(u-7)-3=-3(-6u+3)-6u

Simple and best practice solution for 2(u-7)-3=-3(-6u+3)-6u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(u-7)-3=-3(-6u+3)-6u equation:



2(u-7)-3=-3(-6u+3)-6u
We move all terms to the left:
2(u-7)-3-(-3(-6u+3)-6u)=0
We multiply parentheses
2u-(-3(-6u+3)-6u)-14-3=0
We calculate terms in parentheses: -(-3(-6u+3)-6u), so:
-3(-6u+3)-6u
We add all the numbers together, and all the variables
-6u-3(-6u+3)
We multiply parentheses
-6u+18u-9
We add all the numbers together, and all the variables
12u-9
Back to the equation:
-(12u-9)
We add all the numbers together, and all the variables
2u-(12u-9)-17=0
We get rid of parentheses
2u-12u+9-17=0
We add all the numbers together, and all the variables
-10u-8=0
We move all terms containing u to the left, all other terms to the right
-10u=8
u=8/-10
u=-4/5

See similar equations:

| 5^(2x-6)=1 | | 2(7x-23)=9x-26 | | u/3+15=23 | | –5x2–15x+20=0 | | 5x-54=-8x-93 | | 2(5x+54)=-8x+93 | | –4h−8=6+3h | | 16-64=6m | | 15x-4=145 | | 12k=45 | | 13+n=48 | | 103680=60h | | -15x5=-10x+25 | | 19x=+8 | | m/−7=2/3 | | 64m^2-1/16=0 | | 2(9x-59)=-x+34 | | 4c-60=180 | | (4a)(2a)=100 | | 4a.2a=100 | | 2^x=1÷2 | | Y=-4x^2-1+9 | | 4c–9+5=c | | 9-3(2x-7)=-22 | | 9(3x-)=9(3x+5) | | 21/4+3/4=x | | 16=-14(y+3) | | 8=5(u-2)-8u | | 111=3-6p | | 20g-1(-8g-15)=3(4g-5) | | 111/4=13-4.5s | | 21x-11x=40 |

Equations solver categories